Meeting the global health challenge : the role of the pharmaceutical industry - Leisinger, Klaus M. (2012)
Argues that pharmaceutical companies have a valuable contribution to make in fulfilling the right to health - alongside governments, international organisations, non-governmental organisations (NGOs) and others.